Evaluation of the performance of some Romanian barley genotypes under organic agriculture conditions in South-West Romania - Florica COLĂ; Ioana C. DUNĂREANU; Mugurel COLĂ; Dorina BONEA; Mihai BOTU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2022)
The purpose of this research was to assess certain agronomic traits (grain yield, test weight and protein content) of ten Romanian barley genotypes in order to identify the most suitable genotypes for organic agricultural system. Field experiments were performed for three years under organic culture conditions at Agricultural Research and Development Station (SCDA) Șimnic, Craiova, Dolj County. ANOVA results have showed significant effects of genotype and experimental year on all studied traits and also significant effects of genotype x year interaction on test weight and protein content. On average, the ‘Gabriela’ variety registered the highest grain yield (4.68 t ha-1), this variety being the most stable (CV 19.87%).  The ‘DH 375-4’ line had the highest test weight (65.63 kg hl-1), and the ‘DH 424-1’ line had the highest protein content (10.51%). The plant breeders may use these genotypes depending on the referred direction by means of the breeding program (malt or feed).